Distributed Mutual Exclusion Algorithm with Improved Performance - Maurya A.K.; Kumar A.; Mishra A.K.; Kumar B.; Vishwakarma P. (My University, 2025)
This paper presents a non-token-based algorithm for mutual exclusion in distributed systems in which sites communicate with other sites by message passing. The Ricart–Agrawala algorithm is one of the mutual exclusion algorithms for a distributed system. This algorithm uses message passing concept to decide which site will execute the Critical Section. This algorithm is a modified version of Lamport mutual exclusion algorithm that takes 3(n − 1) numbers of messages to enter into the CS for any site, where n is the number of sites. Ricart–Agrawala algorithm requires 2(n − 1) messages per Critical Section execution. In our proposed algorithm, the number of messages required for any site to enter into the CS will always be less than the number of messages required in Ricart–Agrawala algorithm. We have reduced the number of messages by cleverly removing the number of reply messages for a site that has already executed the CS. © 2019, Springer Nature Singapore Pte Ltd.